PENGUATAN KARAKTER ANAK USIA DINI MELALUI MANAJEMEN BERBASIS NILAI-NILAI ISLAM DI TAMAN KANAK-KANAK AMANAH DESA SUKAJADI KEC. PERBAUNGAN KAB. SERDANG BERDAGAI - Mayang Sari Lubis; Indah Syahputri; Khoirunnisa Lubis; Sheilla Salsabilla; Muhammad Yaqub Hudawi Pasaribu (LPPM IAD Probolinggo, 2026)
This study aims to analyze the implementation of Islamic values-based management in strengthening children’s character at Amanah Kindergarten in Sukajadi Village, Perbaungan Subdistrict, Serdang Bedagai Regency. The study employs a qualitative approach, using data collection techniques such as semi-structured in-depth interviews, non-participatory observation, and document analysis. The results show that the implementation of management based on Islamic values is carried out through various habit-forming programs, such as smiling, greeting, and saying hello (3S), performing prayers, reciting the Iqra’, daily prayers, and cultivating Islamic etiquette in daily life. Character building is also supported through teachers serving as role models and the use of audiovisual learning media, specifically Islamic animated videos featuring stories of the prophets and noble moral values. Factors supporting implementation include support from the principal, teachers, and parents; the availability of facilities and infrastructure; and the use of educational technology. Conversely, inhibiting factors include differences in religious practices within the family environment, the limited attention spans of young children, and challenges in utilizing learning media. The implementation of management based on Islamic values has positive implications for strengthening children’s religious, moral, social, and emotional character, as reflected in attitudes of discipline, honesty, politeness, compassion, responsibility, and the ability to form positive social relationships. The implementation of management based on Islamic values has positive implications for strengthening children’s religious, moral, social, and emotional character, as reflected in their discipline, honesty, politeness, compassion, responsibility, and ability to form positive social relationships. Thus, management based on Islamic values serves as an effective approach to shaping the character of young children so that they possess noble moral character and are able to practice Islamic values in their daily lives.